Notes on the distribution and ecology of the genus Stenelmis Dufour, 1835 (Coleoptera: Elmidae) in the Caucasus - Shapovalov, Maksim I.; Prokin, Alexandr A.; Palatov, Dmitry M.; Kovalev, Alexey V. (Zootaxa, 2015)
The distribution of the genus Stenelmis (Elmidae) of the Caucasus is reviewed based on materials collected by the authors and examined specimens stored in accessible collections. One of the two species present in this region, represented by the subspecies Stenelmis consobrina consobrina Dufour, 1835, is recorded for the first time in Krasnodar Krai and possibly in Armenia; Stenelmis puberula Reitter, 1887 is recorded for the first time in Russia (Krasnodar Krai and the Republic of Adygea) and Abkhazia.